2019
DOI: 10.3390/biomedicines7010007
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Mesenchymal Stem Cells as an Infertility Treatment for Chemotherapy Induced Premature Ovarian Insufficiency

Abstract: Background: Premature ovarian insufficiency (POI) is a challenging disease, with limited treatment options at the moment. Umbilical cord blood mesenchymal stem cells (UCMSCs) have demonstrated promising regenerative abilities in several diseases including POI. Materials and Method: A pre-clinical murine case versus vehicle control randomized study. Two experiments ran in parallel in each of the three groups. The first was to prove the ability of UCMSCs in restoring ovarian functions. The second was to prove im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 27 publications
2
24
0
2
Order By: Relevance
“…Regarding the evaluation of fertility status after the PRP injection, the mating trial retrieved a significantly higher number of healthy litters in both PRP-treated groups compared to the non-treated ones. In agreement with our findings, and having stem cell infusion as the more recent gold standard [ 34 ], Mohamed and colleagues transplanted umbilical cord blood mesenchymal stem cells (UCMSCs) to POI mice, getting a higher number of born litters than in the untreated POI group [ 48 ]. Similar results were obtained as well from Lai and co-workers in 2014 and Su and colleagues in 2016, in where skin derived mesenchymal stem cells (SMSCs) and ADMSCs combined with collagen scaffold were used, respectively [ 8 , 49 ].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the evaluation of fertility status after the PRP injection, the mating trial retrieved a significantly higher number of healthy litters in both PRP-treated groups compared to the non-treated ones. In agreement with our findings, and having stem cell infusion as the more recent gold standard [ 34 ], Mohamed and colleagues transplanted umbilical cord blood mesenchymal stem cells (UCMSCs) to POI mice, getting a higher number of born litters than in the untreated POI group [ 48 ]. Similar results were obtained as well from Lai and co-workers in 2014 and Su and colleagues in 2016, in where skin derived mesenchymal stem cells (SMSCs) and ADMSCs combined with collagen scaffold were used, respectively [ 8 , 49 ].…”
Section: Discussionsupporting
confidence: 88%
“…To date, some studies have indicated that MSCS transplantation can promote ovarian functional restoration in POI mice, as indicated by the recovery of body weight, ovarian weight, hormone levels, and ovarian reserve after stem cell therapy [ 21 , 23 , 32 – 43 ]. However, the mechanisms by which MSCs exert their actions have not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…UCMSCs interact with steroidal hormones by decreasing FSH levels and increasing AMH levels [32]. Treatment with UCMSCs recovers serum hormone levels, and although these levels are not completely within the normal range, they are better than those in the POI group.…”
Section: Potential Therapeutic Effectsmentioning
confidence: 94%